Smart Energy Control Systems for Sustainable Buildings - Littlewood, John.; Spataru, Catalina; Howlett, Robert J.; Jain, Lakhmi C.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
There is widespread interest in the way that smart energy control systems, such as assessment and monitoring techniques for low carbon, nearly-zero energy and net positive buildings can contribute to a Sustainable future, for current and future generations. There is a turning point on the horizon for the supply of energy from finite resources such as natural gas and oil become less reliable in economic terms and extraction become more challenging, and more unacceptable socially, such as adverse public reaction to 'fracking'. Thus, in 2016 these challenges are having a major influence on the design, optimisation, performance measurements, operation and preservation of: buildings, neighbourhoods, cities, regions, countries and continents. The source and nature of energy, the security of supply and the equity of distribution, the environmental impact of its supply and utilization, are all crucial matters to be addressed by suppliers, consumers, governments, industry, academia, and financial institutions. This book entitled 'Smart Energy Control Systems for Sustainable Buildings' contains eleven chapters written by international experts based on enhanced conference papers presented at the Sustainability and Energy in Buildings International conference series. This book will be of interest to University staff and students; and also industry practioners.
From the Content: Zero-Energy Living Lab -- Assessment of the Green Roofs Thermal Dynamic Behaviour for Increasing the Building Energy Efficiencies -- Understanding Opportunities and Barriers for Xocial Occupant Learning in Low Carbon Housing.
Keywords: Computational intelligence; Electric power production; Renewable energy sources; Civil engineering; Computational Intelligence; Electrical Power Engineering; Mechanical Power Engineering; Renewable Energy; Civil Engineering